UPPER EXTREMITY EXAMINATION PROTOCOLS OF GERIATRIC PATIENTS UNDERGOING DIALYSIS (EuroMediterranean Biomedical Journal, 2026)
Many geriatric people experience a certain loss of self sufficiency because of reduced capacities in the use of the upper limbs and, consequently, in the use of the hand. In this connection, the following hypothesis was formulated. Can a moderate physical activity, planned for elderly people in fragile health, in this case, undergoing dialysis, improve their physical capacities and those of their vital functions (strength, mobility, coordination) and some of their haemochemical parameters To study this hypothesis, two groups of people undergoing recurrent dialysis were taken into consideration. The experimental group was made up of twelve people (seven men and five women) and the control group of seven people (five men and two women ) between the ages of 60 and 85. The study protocol successfully demonstrated the validity and the benefits, both physical and psychological, which an elderly person undergoing dialysis can obtain by means of appropriate and constant physical activity.